PENGARUH STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS V PADA MATERI IDE POKOK - Adhiba Anis Safitri; Conny Dian Sumadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low reading comprehension learning outcomes of elementary school students, especially in identifying main ideas. In addition, teachers have not used learning strategies that have not used learning strategies that specifically stimulate reading comprehension learning outcomes. Therefore, the implementation of more effective learning strategies is needed. This study aims to determine the effect of the Directed Reading Thinking Activity (DRTA) strategy on the cognitive learning outcomes of fifth-grade students on the main idea material. This study uses a quantitative approach with an experimental research type and a quasi-experimental design specifically nonequivalent control group design. The independent variable of the study is the DRTA strategy, while the dependent variable is students cognitive learning outcomes. The research sample consisted of fifth-grade students divided into an experimental class and a control class. Data collection techniques used tests, interviews, observations, and documentation. Data analysis techniques were carried out with nonparametric statistical tests to test the research hypothesis. The result showed that there was a significant effect of the use of the DRTA strategy on students cognitive learning outcomes on the main idea material, indicated by the difference in average scores between the experimental class and the control class. Thus, it can be concluded that the directed reading thinking activity strategy has an effect on the cognitive learning outcomes of fifth grade students on the main idea material.